A study of Task Mismatch and its effect on Work Motivation and employee performance - Hasyim, Hasyim; Bakri, Muhammad (Fakultas Ekonomi, Universitas Muslim Indonesia, 2024)
This study examines the impact of training opportunities on employee motivation across various industries, emphasizing intrinsic and extrinsic motivational factors. The research aims to comprehensively understand how tailored training programs can enhance motivation and performance by exploring sectoral differences and individual characteristics. The study employs a qualitative systematic literature review (SLR) to synthesize findings from reputable academic sources. By integrating theoretical frameworks, such as Maslow's Hierarchy of Needs and Herzberg's Two-Factor Theory, the research contextualizes the role of training within diverse industrial settings and identifies key factors influencing its effectiveness. The findings reveal that training significantly enhances intrinsic and extrinsic motivation, with sectoral variations shaping its effectiveness. Training focuses on innovation and adaptability in technology-driven industries, while service sectors emphasize soft skills such as communication and empathy. In contrast, manufacturing prioritizes technical training to ensure operational efficiency and safety. Organizational support and individual characteristics, such as motivational profiles, mediate training outcomes. These results underline the need for personalized and sector-specific training approaches to optimize employee engagement and productivity. This study contributes to the academic understanding of training and motivation by bridging theoretical and practical perspectives. It highlights the importance of using data-driven tools like learning management systems (LMS) to design effective training programs. Managerially, the research underscores the strategic value of aligning training initiatives with organizational goals to foster sustained growth and competitiveness.